The Establishment of a Terrorist Prison: Insights from Indonesian Prison Officers’ Perspectives - Suarda, I Gede Widhiana; Walters, Reece; Priambudi, Zaki (Journal of Indonesian Legal Studies, 2024)
The increasing number of ‘terrorist prisoners’ in Indonesia has resulted in the establishment of a separate penal institution. This development is novel to Indonesian secure settings, and the perceptions of prison officers’ who work in these specialist prisons offer distinct practical insights into the efficacy of these correctional facilities. The present study provides innovative findings by exploring, for the first time, the perspectives of Indonesian prison officers working in specialist prisons for terrorist prisoners in Indonesia. This study conducted focus groups with Indonesian prison officers in Cipinang, Pasir Putih Nusakambangan, and Surabaya prisons. A qualitative content analysis was deployed that identified several themes for future policy decisions. These included, the establishment and ongoing administration of a special prison;, the need to improve data collection of terrorist inmates; the importance of partnerships with key stakeholders, and the centrality of review mechanisms to ensure that processes for prisoner selection, management, and release are optimised and enhanced to ensure future community safety and security.